Osteoporosis in primary biliary cirrhosis revisited. Issue 2 (1st August 2001) - Newton, J; Francis, R; Prince, M; James, O; Bassendine, M; Rawlings, D; Jones, D
Abstract : BACKGROUND: Primary biliary cirrhosis (PBC) is increasingly being diagnosed in the earlier non-cholestatic stages of disease. Accepted wisdom has been that PBC is frequently complicated by osteoporosis. Whether this association holds true for the broader spectrum of PBC patients now recognised has not as yet been studied. AIMS: To examine the extent to which osteoporosis occurs more commonly in PBC patients than in normal individuals of the same age and sex. DESIGN: Retrospective review of a large cohort of well characterised PBC patients. PATIENTS: A total of 272 PBC patients with definite or probable PBC followed up for a mean of 10.1 years (total follow up 2726 patient years) who had at least one bone mineral density measurement (BMD). RESULTS: In this unselected group of PBC patients, mean Z scores (number of SDs from age and sex matched normal mean values) at the neck of femur (NOF) and lumbar spine (LS) at first BMD measurement (7 (6) years after PBC diagnosis) were −0.1 (1.4) and 0.1 (1.4), respectively. At first BMD measurement, 18 PBC patients had Z scores less than −2.0 and 85 had T scores less than −2.5. No factors predictive of osteoporosis were found in affected patients. A total of 957 BMD measurements were performed (0.35 per patient year of follow up); 220 patients had two or more measurements. No patient went on to develop de novo osteoporosis during follow up. In the 51 patients (who were clinically representative of the whole group) who received no PBC or bone related treatment during follow up, %BMD changes per year at the NOF and LS were −1.6 (3.2) and 0.1 (2.2), respectively. No variance in this "natural" rate of BMD measurement was seen in patients receiving PBC modulating agents (including prednisolone and UDCA) or osteoporosis prophylaxis/therapy. Significant improvement at the LS was seen in patients undergoing liver transplantation. CONCLUSIONS: Osteoporosis is not a specific complication of PBC.